Zein patterns as effective markers of valuable agronomic traits in maize - V. V. Sidorova; A. V. Konarev; Yu. A. Kerv (Труды по прикладной ботанике, генетике и селекции)
The effective use of maize (Zea mays L.) in agriculture depends entirely on the knowledge of its gene pool, which, in turn, needs to undergo registration and certification as new data become available. Maize is one of the model objects for applying the marker methodology. This article summarizes the results of a long-term study of the maize gene pool at N. I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) in two main areas: identification of the world genetic diversity of maize (including the most important wild relatives for breeding use), and search for reliable protein (zein) markers of traits valuable for breeding in order to use them in improvement, seed production, and seed control of this crop. Specific examples show the effectiveness of using zein markers in the development of new inbred lines and improvement of the existing ones. On the examples of such agronomic traits as early maturity, explosiveness, and waxiness of maize grain, the possibility of controlling the “inclusion” of these traits in the breeding material with the help of zein markers has been demonstrated. Evidence of the effectiveness of applying zein markers in the selection of parental pairs to obtain highly heterotic hybrids is presented. The nomenclature of zein adopted at VIR after its separation by polyacrylamide gel electrophoresis (PAGE) in an acidic buffer was compared with the nomenclature of zein after polyacrylamide gel electrophoresis with sodium dodecyl sulfate (SDS-PAGE) adopted among the foreign scientific community. The studies were performed on a large volume of accessions from the VIR collection as well as on breeding material provided by the country’s leading breeders.